2021
DOI: 10.1016/j.ynstr.2021.100325
|View full text |Cite
|
Sign up to set email alerts
|

κ-Opioid receptor antagonism reverses heroin withdrawal-induced hyperalgesia in male and female rats

Abstract: Although opioids are potent analgesics, a consequence of chronic opioid use is hyperalgesia during withdrawal, which may contribute to opioid misuse. Dynorphin, the endogenous ligand of κ-opioid receptors (KORs), is upregulated in opioid-dependent rats and in animal models of chronic pain. However, the role of KORs in opioid withdrawal-induced hyperalgesia remains to be determined. We hypothesized that KOR antagonism would reverse opioid withdrawal-induced hyperalgesia in opioid-dependent rats. Male and female… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 91 publications
1
17
1
Order By: Relevance
“…Although some studies identified sex differences in hyperalgesia during heroin withdrawal in rats ( Marchette et al, 2021 ), we did not find sex differences in the present study in mice. In addition to species differences and specific timepoints of behavior assessment, the lack of sex differences in the present study may have resulted from the use of relatively high doses of heroin in both male and female mice (40–50 mg/kg twice daily).…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Although some studies identified sex differences in hyperalgesia during heroin withdrawal in rats ( Marchette et al, 2021 ), we did not find sex differences in the present study in mice. In addition to species differences and specific timepoints of behavior assessment, the lack of sex differences in the present study may have resulted from the use of relatively high doses of heroin in both male and female mice (40–50 mg/kg twice daily).…”
Section: Discussioncontrasting
confidence: 99%
“…Both distinct and similar cellular and molecular mechanisms have been linked to hyperalgesia and somatic withdrawal ( Maldonado et al, 1996 ; Largent-Milnes et al, 2008 ; Tsai et al, 2009 ; Corder et al, 2013 ; Brust et al, 2015 ). For example, κ-opioid receptor antagonism reversed hyperalgesia during spontaneous heroin withdrawal in male and female rats but did not affect somatic withdrawal ( Marchette et al, 2021 ). However, antagonists of NMDA glutamate receptors, β2-adrenergic receptors, serotonin 5-hydroxytryptamine-3 (5-HT 3 ) receptors, and corticotropin-releasing factor 1 (CRF 1 ) receptors attenuated both somatic withdrawal ( Pinelli et al, 1997 ; Lu et al, 2000 ; Liang et al, 2007 ; Higgins et al, 2019 ) and hyperalgesia ( Higgins et al, 1992 ; Liang et al, 2006 , 2011 ; Harris et al, 2008 ; Park et al, 2015 ) in male rats and mice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…18 KOR antagonism was also recently shown to reverse heroin withdrawal-induced hyperalgesia in male and female rats. 19 These results suggested that antagonizing KOR may halt some depressive and anxiety-related symptoms that are associated with withdrawal, along with motivational withdrawal symptoms, to ultimately reduce drug use relapse.…”
Section: Introductionmentioning
confidence: 95%
“…17 KOR antagonism was also recently shown to reverse heroin withdrawal-induced hyperalgesia in male and female rats. 18 These results suggested that antagonizing KOR may halt some depressive and anxiety-related symptoms that are associated with withdrawal, along with motivational withdrawal symptoms, to ultimately reduce drug use relapse.…”
Section: Introductionmentioning
confidence: 95%